The Implementation of Islamic Religious Education (PAI) in Shaping the Profile of Rahmatan lil alamin Students in a Madrasah - Khoirul Muthrofin; Hepi Ikmal; Winarto Eka Wahyudi (STAI Miftahul Ula Nganjuk, 2025)
Religious Education plays a crucial role in shaping the personality of students. An ideal Islamic Religious Education (PAI) should not merely focus on the transmission of religious knowledge but also encompass learning to practice the acquired religious knowledge and instilling Islamic values (value transfer) that align with the concept of